Cushing's like syndrome in typical bronchial carcinoid a case report and review of the literature. (2016) - Pedicelli, Ilaria; Patriciello, Giuseppina; Scala, Giovanni; Sorrentino, Antonietta; Gravino, Gennaro; Patriciello, Pasquale; Zeppa, Pio; Di Crescenzo, Vincenzo; Vatrella, Alessandro
Abstract: Cushing's syndrome occurred in 1–5% of cases of bronchial carcinoids. In this paper we describe a case of typical bronchial carcinoid in a nonsmoker young male with clinical manifestations mimicking a Cushing's syndrome. The patient performed chest radiograph and computed tomography. Fiberoptic bronchoscopy revealed the presence of an endobronchial mass occluding the bronchus intermedius. A rigid bronchoscopy was necessary for the conclusive diagnosis and for partial resection of the intraluminal tumor. Despite of the presence of Cushingoid features, the normal blood levels of ACTH and cortisol excluded the coexistence of a Cushing's syndrome.